Effect of Work Stress and Burnout Perceptions of Aviation Sector Employees on Organizational Commitment - DURSUN, DR. ERDAL (The journal of contemporary issues in business and government, 2021)
Aviation sector employees, who have an important role in the aviation industry, wear out both physically and psychologically due to the heavy working conditions of their work and the difficulties of working in the service sector. These difficulties cause stress and burnout on employees, such as intense competition, high performance and productivity expectations, time pressure and excessive workload. Hence, the commitment of the employees to their organizations decreases over time. As a result of preventing work stress, there may be a decrease in the burnout levels of the employees and an increase in the organizational commitment of the employees.